Absence of the RING domain in MID1 results in patterning defects in the developing human brain - Frank, Sarah; Gabassi, Elisa; Käseberg, Stephan; Bertin, Marco; Zografidou, Lea; Pfeiffer, Daniela; Brennenstuhl, Heiko; Falk, Sven; Karow, Marisa; Schweiger, Susann (Life Science Alliance, 2024)
The X-linked form of Opitz BBB/G syndrome (OS) is a monogenic disorder in which symptoms are established early during embryonic development. OS is caused by pathogenic variants in the X-linked gene MID1 Disease-associated variants are distributed across the entire gene locus, except for the N-terminal really interesting new gene (RING) domain that encompasses the E3 ubiquitin ligase activity. By using genome-edited human induced pluripotent stem cell lines, we here show that absence of isoforms containing the RING domain of MID1 causes severe patterning defects in human brain organoids. We observed a prominent neurogenic deficit with a reduction in neural tissue and a concomitant increase in choroid plexus-like structures. Transcriptome analyses revealed a deregulation of patterning pathways very early on, even preceding neural induction. Notably, the observed phenotypes starkly contrast with those observed in MID1 full-knockout organoids, indicating the presence of a distinct mechanism that underlies the patterning defects. The severity and early onset of these phenotypes could potentially account for the absence of patients carrying pathogenic variants in exon 1 of the MID1 gene coding for the N-terminal RING domain.
CRIS-Team Scopus Importer:2024-02-02

Cellular identity through the lens of direct lineage reprogramming - Falk, Sven; Han, Dandan; Karow, Marisa (Current Opinion in Genetics & Development, 2021)
Direct lineage reprogramming challenges our traditional view on basic aspects of cellular identity, and in particular on processes crucial for identity acquisition. This is partly because in direct lineage reprogramming but not during natural differentiation processes changing cellular identity can occur in the absence of mitosis. Only recently, technologies emerged to deconstruct the cellular and molecular processes governing the transitory states a cell passes through on the journey from its original identity to the new target cell fate. Here we discuss arising concepts on the nature of these transitory states and the challenges and decisions cells must conquer to reach their new cellular identity.
CRIS-Team Scopus Importer:2021-08-20

Centrosomal microtubule nucleation regulates radial migration of projection neurons independently of polarization in the developing brain - Vinopal, Stanislav; Dupraz, Sebastian; Alfadil, Eissa; Pietralla, Thorben; Bendre, Shweta; Stiess, Michael; Falk, Sven; Ortega, German Camargo; Maghelli, Nicola; Tolic, Iva M.; Smejkal, Jiri; Goetz, Magdalena; et al. (Neuron, 2023)
Cortical projection neurons polarize and form an axon while migrating radially. Even though these dynamic processes are closely interwoven, they are regulated separately-the neurons terminate their migration when reaching their destination, the cortical plate, but continue to grow their axons. Here, we show that in rodents, the centrosome distinguishes these processes. Newly developed molecular tools modulating centrosomal microtubule nucleation combined with in vivo imaging uncovered that dysregulation of centro-somal microtubule nucleation abrogated radial migration without affecting axon formation. Tightly regu-lated centrosomal microtubule nucleation was required for periodic formation of the cytoplasmic dilation at the leading process, which is essential for radial migration. The microtubule nucleating factor g-tubulin decreased at neuronal centrosomes during the migratory phase. As distinct microtubule networks drive neuronal polarization and radial migration, this provides insight into how neuronal migratory defects occur without largely affecting axonal tracts in human developmental cortical dysgeneses, caused by mutations in g-tubulin.
CRIS-Team WoS Importer:2023-05-26

Dentate gyrus astrocytes exhibit layer-specific molecular, morphological and physiological features - Karpf, Julian; Unichenko, Petr; Chalmers, Nicholas; Beyer, Felix; Wittmann, Marie-Theres; Schneider, Julia; Fidan, Elif; Reis, André; Beckervordersandforth, Jan; Brandner, Sebastian; Liebner, Stefan; Falk, Sven; et al. (Nature Neuroscience, 2022)
Neuronal heterogeneity has been established as a pillar of higher central nervous system function, but glial heterogeneity and its implications for neural circuit function are poorly understood. Here we show that the adult mouse dentate gyrus (DG) of the hippocampus is populated by molecularly distinct astrocyte subtypes that are associated with distinct DG layers. Astrocytes localized to different DG compartments also exhibit subtype-specific morphologies. Physiologically, astrocytes in upper DG layers form large syncytia, while those in lower DG compartments form smaller networks. Astrocyte subtypes differentially express glutamate transporters, which is associated with different amplitudes of glutamate transporter-mediated currents. Key molecular and morphological features of astrocyte diversity in the mice DG are conserved in humans. This adds another layer of complexity to our understanding of brain network composition and function, which will be crucial for further studies on astrocytes in health and disease.
CRIS-Team Scopus Importer:2022-12-09

Human Induced Pluripotent Stem Cell-Derived Pericytes as Scalable and Editable Source to Study Direct Lineage Reprogramming Into Induced Neurons - Menon, Radhika; Petrucci, Linda; Lohrer, Benjamin; Zhang, Jingzhong; Schulze, Markus; Schichor, Christian; Winner, Beate; Winkler, Jürgen; Riemenschneider, Markus J.; Kühn, Ralf; Falk, Sven; Karow, Marisa (Cellular Reprogramming, 2023)
Studying human somatic cell-to-neuron conversion using primary brain-derived cells as starting cell source is hampered by limitations and variations in human biopsy material. Thus, delineating the molecular variables that allow changing the identity of somatic cells, permit adoption of neuronal phenotypes, and foster maturation of induced neurons (iNs) is challenging. Based on our previous results that pericytes derived from the adult human cerebral cortex can be directly converted into iNs (Karow et al., 2018; Karow et al., 2012), we here introduce human induced pluripotent stem cell (hiPSC)-derived pericytes (hiPSC-pericytes) as a versatile and more uniform tool to study the pericyte-to-neuron conversion process. This strategy enables us to derive scalable cell numbers and allows for engineering of the starting cell population such as introducing reporter tools before differentiation into hiPSC-pericytes and subsequent iN conversion. Harvesting the potential of this approach, we established hiPSC-derived human-human neuronal cocultures that not only allow for independent manipulation of each coculture partner but also resulted in morphologically more mature iNs. In summary, we exploit hiPSC-based methods to facilitate the analysis of human somatic cell-to-neuron conversion.
CRIS-Team Scopus Importer:2023-11-03
Keywords: direct lineage reprogramming; induced neurons; organoids; pericytes

Repetitive injury and absence of monocytes promote astrocyte self-renewal and neurological recovery - Lange Canhos, Luisa; Chen, Muxin; Falk, Sven; Popper, Bastian; Straub, Tobias; Götz, Magdalena; Sirko, Swetlana (Glia, 2020)
Unlike microglia and NG2 glia, astrocytes are incapable of migrating to sites of injury in the posttraumatic cerebral cortex, instead relying on proliferation to replenish their numbers and distribution in the affected region. However, neither the spectrum of their proliferative repertoire nor their postinjury distribution has been examined in vivo. Using a combination of different thymidine analogs and clonal analysis in a model of repetitive traumatic brain injury, we show for the first time that astrocytes that are quiescent following an initial injury can be coerced to proliferate after a repeated insult in the cerebral cortex grey matter. Interestingly, this process is promoted by invasion of monocytes to the injury site, as their genetic ablation (using CCR2−/− mice) increased the number of repetitively dividing astrocytes at the expense of newly proliferating astrocytes in repeatedly injured parenchyma. These differences profoundly affected both the distribution of astrocytes and recovery period for posttraumatic behavior deficits suggesting key roles of astrocyte self-renewal in brain repair after injury.
CRIS-Team Scopus Importer:2020-08-07
Keywords: astrocyte topology; cognitive disfunction; inflammation; reactive gliosis; self-renew; TBI

The transcriptional co-activator Yap1 promotes adult hippocampal neural stem cell activation - Fan, Wenqiang; Jurado-Arjona, Jerónimo; Alanis-Lobato, Gregorio; Péron, Sophie; Berger, Christian; Andrade-Navarro, Miguel A.; Falk, Sven; Berninger, Benedikt (EMBO Journal, 2023)
Most adult hippocampal neural stem cells (NSCs) remain quiescent, with only a minor portion undergoing active proliferation and neurogenesis. The molecular mechanisms that trigger the transition from quiescence to activation are still poorly understood. Here, we found the activity of the transcriptional co-activator Yap1 to be enriched in active NSCs. Genetic deletion of Yap1 led to a significant reduction in the relative proportion of active NSCs, supporting a physiological role of Yap1 in regulating the transition from quiescence to activation. Overexpression of wild-type Yap1 in adult NSCs did not induce NSC activation, suggesting tight upstream control mechanisms, but overexpression of a gain-of-function mutant (Yap1-5SA) elicited cell cycle entry in NSCs and hilar astrocytes. Consistent with a role of Yap1 in NSC activation, single cell RNA sequencing revealed a partial induction of an activated NSC gene expression program. Furthermore, Yap1-5SA expression also induced expression of Taz and other key components of the Yap/Taz regulon that were previously identified in glioblastoma stem cell-like cells. Consequently, dysregulated Yap1 activity led to repression of hippocampal neurogenesis, aberrant cell differentiation, and partial acquisition of a glioblastoma stem cell-like signature.
CRIS-Team Scopus Importer:2023-05-05
Keywords: hippocampus; neurogenesis; quiescence; radial glia; single cell RNA sequencing